The silent menace: Worm bezoar causing acute intestinal obstruction - Shiva Shiva; Sahil Kumar; Pankaj Singh; Sanjeev Kumar; Suresh Kumar (Journal of Family Medicine and Primary Care)
Intestinal obstruction represents a critical surgical emergency with a myriad of potential causes, ranging from mechanical blockages to functional impairments. In contrast to developed nations, where the usual causes of obstruction are adhesions, strictures, and metabolic derangements, infective etiologies, like tuberculosis and parasitic infestations, are more common in developing countries. We present a case report of a 22-year-old man presenting with acute intestinal obstruction due to a massive ascariasis infestation. The patient exhibited classical symptoms of intestinal obstruction, including abdominal pain, distension, and vomiting. Imaging studies revealed multiple air–fluid levels, suggesting a small bowel obstruction. Emergency surgical intervention was performed, and a substantial number of live worms were extracted from the small intestine, relieving the obstruction. Postoperative recovery was uneventful, and the patient was discharged with anthelmintic therapy and instructions for improved sanitation practices. This case underscores the importance of considering worm bezoars as a differential diagnosis in patients presenting with acute intestinal obstruction, particularly in endemic regions, and highlights the significance of prompt surgical intervention for resolution. Additionally, it emphasizes the critical role of public health measures in preventing and managing parasitic infestations.